(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Prayer is an obligatory act of worship for Muslims. Prayer requires discipline in both the timing and implementation of the prayer. To foster discipline in praying in children, parents should do this from an early age, but in reality there are still elementary school students who are not disciplined in praying. Therefore, an innovation was created in the form of a control book to control student discipline in prayer services involving the class teacher and student guardian. The purpose of this research is to determine the basis and purpose of use, and evaluate the use of control book media at SD Negeri 13 Padang Panjang Timur. This research uses qualitative methods with a descriptive approach. The research results show that (1) The application of control book media aims to overcome problems such as difficulty controlling the class, students individualistic nature, and lack of awareness of congregational prayers. By using control books, students are expected to be more disciplined in worship and understand Islamic teachings. (2) The process of use includes filling in the book after worship, inspection by parents, and assessment by the teacher. (3) evaluations show increased student awareness, discipline, and motivation, with support from teachers, parents, and peers playing an important role in the success of the program. The results of the interview show that the application of control book nedia is effective in improving the prayer discipline of grade 4 students at SD Negeri 13 Padang Panjang Timur.